Worldwide trends and orientations of raising goats - Rodica Chetroiu; Ion Călin; Carmen Georgeta Niculescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Worldwide, raising goats had generally an ascending trend, both in terms of stocks and the production level. Thus, according to FAO statistics, in 2011 there were over 875.5 million heads of goats. The largest number of goats was in the year 2011 in Asia - over 539 million heads, representing 61.6% of the total, followed by Africa with over 276 million heads, holding a share of 31.6% of livestock globally. At European level, in 2011, the largest goat populations were in Greece and Romania ranks the fifth continental level, with about 1.24 million heads. If in 2000 the production of goat milk globally was 12.78 million tons, in 2011 it reached an amount of 15.86 million tons, registering a growth rate of over 24%. The general trends of goat production systems are increasing size of farms, while reducing their number, decreasing pastoral practices in the milk production, enlarging the stocks of major milk producing breeds and increasing the number of projects for the conservation of local breeds.
Keywords: 330; goats; trends; heads; milk; production